Causes of the reduction in immunization rates among children in the municipality of Cascavel and their implications on public health in Brazil in disease prevention (Research, Society and Development, 2024)
Introduction: Vaccination is essential to prevent serious diseases and their spread. Despite the broad National Immunization Program (PNI) in Brazil, childhood vaccination rates have fallen, increasing the risk of a resurgence of eradicated diseases. It is crucial to promote awareness about the importance of vaccination and the cause of this reduction to ensure the protection of the entire population.Objective: To establish the causes of the reduction in the immunization rate among children up to 12 years of age in the municipality of Cascavel and analyze the future implications for general public health in Brazil. Methodology: Quantitative and qualitative cross-sectional study, focusing on collecting data by applying a questionnaire via the Google Forms® platform, aimed at parents or guardians of children aged 0 to 12, regardless of gender and different regions of the municipality of Cascavel. Results: 160 responses to the questionnaire were analyzed. Of these 160 responses, 100% of guardians had vaccinated their children, but of the 59 who were questioned, 60.3% claimed that someone they knew had already stopped immunizing the children under their care. It is worth mentioning that although 86% of employees have already sought information about vaccinations and 95% consider them truly effective, 46.3% have already felt some type of insecurity regarding immunizations and 70% have read and recognized some type of fake news, disseminated mainly through social networks, as the research shows. Conclusion: with this study, it is concluded that despite the broad knowledge available in relation to immunization agents, there is still hesitation regarding vaccination, triggered both by fake news and also by a lack of knowledge, fear and mainly insecurity regarding its side effects. diagnosis are important factors that influence the prognosis and survival of patients with medulloblastoma, for this reason, studies on this disease are extremely important.